Transition metal oxide@hzsm-5 / sba-15 composite catalysts, their preparation and use in the synthesis of fdca

CN118437389BActive Publication Date: 2026-10-30CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410467436.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2026-10-30
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

[0007]针对现有HMF催化氧化制备FDCA体系中以贵金属催化剂为主的高成本问题以及催化剂载体效应弱的问题,本发明的目的在于提供一种过渡金属氧化物@HZSM-5/SBA-15复合催化剂的制备方法,旨在基于低成本工艺和原料制备得到适配HMF催化氧化成FDCA的高活性和选择性的负载型催化剂

Benefits of technology

[0036]本发明创新地采用HZSM-5、SBA-15和过渡金属源复合后进行焙烧处理,如此能够意外地实现协同,能够改善金属颗粒的分散程度及其之间的界面作用,并能够暴露更多的活性位点,进而使其表现出更优的HMF催化氧化活性以及FDCA的产物选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118437389B_ABST
    Figure CN118437389B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of composite catalytic materials, specifically to transition metal oxide @ HZSM-5 / SBA-15 composite catalyst and its preparation and application in FDCA synthesis, the preparation method of the transition metal oxide @ HZSM-5 / SBA-15 composite catalyst described in the present application, HZSM-5, SBA-15 and transition metal source are compounded after calcination treatment at ≥350 ℃ temperature, it is obtained;The transition metal element in the transition metal source includes at least one of iron, chromium, cobalt, manganese;The weight ratio of HZSM-5, SBA-15 is 1 ~ 3:1 ~ 2;The loading of transition metal element in transition metal source in transition metal oxide @ HZSM-5 / SBA-15 composite catalyst is 5 ~ 15 wt.%.The present application innovatively uses the synergistic composite of HZSM-5, SBA-15, cooperates combined transition metal, can further realize synergy, can unexpectedly improve the interface, crystal phase and active site of material, and then can unexpectedly synergistically improve the catalytic oxidation activity of HMF, improve the selectivity of FDCA.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite catalytic material, specifically to a catalyst for the synthesis of FDCA. Background Technology

[0002] The world's current energy system urgently needs new energy sources that combine both renewable and environmentally friendly attributes to replace fossil fuels and produce a range of high-value chemicals and clean fuels. Biomass is the only renewable green organic carbon source in nature, effectively overcoming dependence on fossil fuels. Lignocellulose, the main structural component of plants, is the most abundant renewable resource to date, showing promising applications in the conversion into biofuels, functional materials, and chemicals, such as bioethanol, 5-hydroxymethylfurfural (HMF), phenols, and other commercial chemicals. HMF is a bio-platform molecule derived from lignocellulose and is a raw material for many important chemicals, such as γ-valerol (GVL) for producing high-value fuels and polyvinyl alcohol (PVA) for battery manufacturing. In particular, 2,5-furandicarboxylic acid (FDCA), obtained from its oxidation, is one of the 12 high-value bio-based platform compounds proposed by the U.S. Department of Energy, and its polyester products are widely used in biomedicine, food, and other fields. In particular, polyethylene furanate (PEF), which is polymerized with ethylene glycol, has the ability to replace polyethylene terephthalate (PET), the main raw material for plastic production.

[0003] Currently, the catalytic pathways for preparing FDCA from HMF can be broadly categorized into four types: thermocatalysis, electrocatalysis, photocatalysis, and biocatalysis. Considering industrial compatibility, yield, and product purity, thermocatalysis remains the most popular conversion method, and it can be further divided into homogeneous and heterogeneous catalysis. The former utilizes catalysts such as inorganic acids and ionic liquids. While these catalyst systems exhibit uniform active sites and clear structures, catalyst separation in the reaction mixture is difficult, potentially leading to side reactions and significantly reduced catalyst recovery performance. The latter, represented by metal oxides, metal carbides, and functional carbon materials, creates an environment where multiple active sites coexist, which is beneficial for improving catalytic efficiency.

[0004] Currently, my country still faces certain challenges in achieving the industrialization of FDCA, indicating significant room for development. There is an urgent need to construct a highly efficient, economical catalytic system with good catalyst stability, mild reaction conditions, and suitability for large-scale production. Supported catalysts, as typical heterogeneous catalysts, can not only reduce the cost of using only active materials as catalysts but also further reduce costs and achieve high-efficiency conversion by combining non-precious metals or even environmentally friendly non-metallic components with suitable supports. Therefore, the first consideration is the selection of the support. Often, a type of solid porous material with high surface area, suitable pore size and distribution, and sufficient pore volume is used, and the support becomes even more advantageous after being composited or modified. Among these, molecular sieves, due to their unique structural characteristics, are widely used in catalysis research. Regarding the selection of active components, current systems for preparing FDCA still primarily rely on noble metals. For example, Chinese patent document CN109046349A discloses a single-atom palladium catalyst for the catalytic oxidation of 5-HMF to prepare 2,5-FDCA. The catalyst structure is as follows: the active component palladium is highly dispersed and uniformly distributed on the surface of manganese dioxide in a single-atom manner; wherein the palladium content is 0.2–3 wt%, and the manganese dioxide content is 97–99.8 wt%. Noble metal catalysts can achieve good results, but they are costly. Therefore, the selection of low-cost and efficient non-metallic components for catalyst synthesis is one of the hot topics in the conversion of HMF to FDCA.

[0005] With the continuous updating of technology, existing literature has also reported some non-precious metal catalytic methods. For example, Chinese patent document with publication number CN105418561A discloses a method for preparing 2,5-furandicarboxylic acid from fructose using a supported bifunctional catalyst. The catalyst is a support for heteropolyacids and their salts or hydrates, wherein the heteropolyacids and their salts or hydrates are any one or more of K6[CoIIw12O40]·16H2O, K5[CoIIIw12O40]·20H2O, Co2H9P2Mo15V3O62, and (NH4)3[CoMo6O24H6]·7H2O.

[0006] Although existing catalyst improvement methods can improve the preparation effect of FDCA to a certain extent and enhance its application capability, the cost of catalysts is still high, the structural controllability is poor, and there is still considerable room for improvement in the conversion rate and selectivity of FDCA products. Summary of the Invention

[0007] To address the high cost and weak catalyst support effect of existing HMF catalytic oxidation to FDCA systems, which are dominated by noble metal catalysts, the present invention aims to provide a method for preparing a transition metal oxide@HZSM-5 / SBA-15 composite catalyst. This method aims to obtain a highly active and selective supported catalyst suitable for the catalytic oxidation of HMF to FDCA based on low-cost processes and raw materials.

[0008] The second objective of this invention is to provide a transition metal oxide@HZSM-5 / SBA-15 composite catalyst prepared by the aforementioned method.

[0009] A third objective of this invention is to provide a method for preparing FDCA by catalytic oxidation of HMF using the aforementioned transition metal oxide@HZSM-5 / SBA-15 composite catalyst, with the aim of improving the yield and selectivity of FDCA.

[0010] Selective catalytic oxidation of HMF is a common method for preparing FDCA, but this reaction suffers from problems such as low HMF conversion, easy introduction of impurities such as formic acid and levulinic acid, and unsatisfactory selectivity of FDCA. To address these issues, this invention, through in-depth research, provides the following improved solutions:

[0011] The preparation method of the transition metal oxide@HZSM-5 / SBA-15 composite catalyst involves calcining HZSM-5, SBA-15 and a transition metal source at a temperature of ≥350℃.

[0012] The transition metal element in the transition metal source includes at least one of iron, chromium, cobalt, and manganese;

[0013] The weight ratio of HZSM-5 to SBA-15 is 1-3:1-2;

[0014] The loading of transition metal elements in the transition metal source in the transition metal oxide@HZSM-5 / SBA-15 composite catalyst is 5–15 wt.%.

[0015] This invention innovatively employs HZSM-5, SBA-15, and a transition metal source in combination followed by calcination treatment. This unexpectedly achieves synergy, improving the dispersion of metal particles and their interfacial interactions, and exposing more active sites, thereby exhibiting superior HMF catalytic oxidation activity and FDCA product selectivity.

[0016] In this invention, the combined in-situ calcination of HZSM-5 and SBA-15 is key to synergistically improving their HMF catalytic activity and FDCA product selectivity. Furthermore, research indicates that optimizing parameters such as the proportion of the support, the type of transition metal, and the loading amount can further enhance process synergy and is expected to further improve FDCA yield.

[0017] Preferably, the weight ratio of HZSM-5 to SBA-15 is 1.5–2.5:1, more preferably 1.9–2.1:1. Studies have shown that at this preferred ratio, it can be further combined and synergistically processed with other processes to help improve the yield of the prepared material in the FDCA synthesis process.

[0018] In this invention, the transition metal element in the transition metal source includes two or more of iron, chromium, cobalt, and manganese. More specifically, the transition metal element in the transition metal source includes cobalt and manganese; furthermore, the weight ratio of cobalt to manganese is 1–2:1–2. Studies have shown that, based on the synergistic effect of HZSM-5 and SBA-15, further combining cobalt and manganese can unexpectedly achieve synergy, significantly improving the conversion rate and selectivity of the catalyst in FDCA preparation.

[0019] This invention also shows that, with the innovative combination of HZSM-5 and SBA-15, and further combined with the aforementioned composite metal, the interface and active site distribution of the components can be further improved, achieving solid solution activation of the particles, thereby further improving the product conversion rate and selectivity of FDCA.

[0020] In this invention, the water-soluble salt of the transition metal element is preferably at least one of the transition metal element's nitrate, sulfate, organic acid salt, and chloride salt;

[0021] Preferably, the composite method is solid-phase composite or wet impregnation. In this invention, the wet impregnation process involves, for example, mixing the HZSM-5, SBA-15, and transition metal source in a liquid phase, followed by solvent removal to obtain the composite. In this invention, the impregnation solvent is not particularly required, as long as it can dissolve the transition metal source; for example, it can be water.

[0022] In this invention, the loading of transition metal elements is preferably controlled at 8 to 12 wt.%, more preferably 9 to 11 wt.%.

[0023] In this invention, the composite material is innovatively subjected to calcination treatment. In this invention, the calcination atmosphere is an oxygen-containing atmosphere, preferably an air atmosphere.

[0024] Preferably, the calcination temperature is 350–500°C, and more preferably 400–450°C;

[0025] Preferably, the roasting time is 2 to 5 hours.

[0026] The present invention also provides a transition metal oxide@HZSM-5 / SBA-15 composite catalyst prepared by the aforementioned method.

[0027] In this invention, thanks to the combination of the preparation methods, the material can be endowed with special physicochemical structural characteristics, and the material with special characteristics obtained by the preparation methods can unexpectedly improve the catalytic oxidation activity of HMF and improve the selectivity of FDCA.

[0028] This invention also provides a method for synthesizing FDCA, which involves catalytically oxidizing HMF, a base, an oxidant, and a catalyst to obtain FDCA; wherein the catalyst is the transition metal oxide@HZSM-5 / SBA-15 composite catalyst obtained in this invention.

[0029] In the preparation process of FDCA described in this invention, apart from the catalyst described in this invention, all other parameters and conditions can be known or reasonably controlled based on known principles.

[0030] For example, in this invention, the alkali is at least one of an alkali metal bicarbonate and ammonia water;

[0031] The weight ratio of HMF, base, and catalyst is 1:1.25-3:0.5-1.5;

[0032] In this invention, the oxidant is at least one oxidant that is in the form of gas, liquid, or solid. When it is a gaseous oxidant, the oxygen partial pressure during the catalytic oxidation stage is controlled to be 0.6–1.8 MPa, and more specifically, 1–1.2 MPa.

[0033] In this invention, the temperature of the catalytic oxidation reaction is 100–160°C, more preferably 130–150°C.

[0034] In this invention, the catalytic oxidation reaction takes 8 hours or more, preferably 10 to 24 hours.

[0035] Beneficial effects

[0036] This invention innovatively employs HZSM-5, SBA-15, and a transition metal source in combination followed by calcination treatment. This unexpectedly achieves synergy, improving the dispersion of metal particles and their interfacial interactions, and exposing more active sites, thereby exhibiting superior HMF catalytic oxidation activity and FDCA product selectivity.

[0037] In this invention, the synergistic combination of HZSM-5 and SBA-15, along with the accompanying transition metals, further enhances the synergistic effect, unexpectedly improving the material's interface, crystal phase, and active sites. This, in turn, unexpectedly improves the catalytic oxidation activity of HMF and the selectivity of FDCA. Building upon this innovation, further incorporating Co / Mn as the combined transition metals unexpectedly further enhances the synergistic improvement in FDCA conversion and selectivity. Attached Figure Description

[0038] Figure 1 The images show SEM images (a) of the HZSM-5 and SBA-15 composite support with a weight ratio of 2:1 (Z:S = 2:1) and TEM images (b) of the cobalt-loaded catalyst Co with a Z:S = 2:1 weight ratio in Example 1. Figure 1 (a) It can be seen that the surface of SBA-15, which is composed of stacked tubular pore structures, contains blocky HZSM-5. Both molecular sieves contain abundant sites on their surfaces and within their pores that can bind to the active components. Figure 1 (b) The degree of bonding between the two molecular sieves and the bonding sites of the loaded cobalt metal active components can be further observed.

[0039] Figure 2 The FT-IR images are those of HZSM-5, SBA-15, Z:S = 2:1, and Co-Z:S = 2:1 mentioned in Example 1. At 799 cm⁻¹ -1 1086cm -1 The wavelength band is due to the symmetric / antisymmetric stretching vibration of the Si-O-Si bond, at 451 cm⁻¹. -1 The location is due to the bending vibration of the Si-O-Si bond, 547 cm. -1 The presence of Al-O bonds is indicated at 3700-3200 cm. -1 The absorption region is characterized by hydroxyl groups, containing Si-OH, Al-OH, or hydrogen-bonded hydroxyl groups. After composite treatment, the wavelength intensity of the hydroxyl region falls between that of the two molecular sieves, and the enhancement of the Si-O-Si bond wavelength indicates successful composite support preparation. Furthermore, after loading the active component, the absorption intensity at 520-560 cm⁻¹... -1 Co at the place 2+ The absorption peak of -O overlaps with the Al-O bond region in the spectrum, and the waveform is deeper; and at 667 cm⁻¹... -1 Co at the place 3+ -O further confirms the successful preparation of the catalyst.

[0040] Figure 3 (a) shows the XRD patterns of HZSM-5, SBA-15, Z:S = 2:1 and Co-Z:S = 2:1 in Example 1. Figure 3 (b) and Figure 3 (c) are the low-angle XRD patterns of SBA-15 and Co-Z:S = 2:1, respectively. It can be seen that the composite support Z:S-2:1 exhibits characteristic peaks of both ZSM-5 and SBA-15, indicating that the original structures of the two molecular sieves remained essentially unchanged after composite treatment, consistent with the SEM results. The characteristic peaks at 2θ = 19°, 31.2°, 36.8°, 59.3°, and 65.2° in the figure can be attributed to Co3O4 (JCPDS43-1003). In particular, the cell volume of SBA-15 causes its diffraction peaks to only diffract at low angles in the XRD pattern. Figure 3 (b) The presence of Co particles on the SBA-15 surface causes the crystal planes (110) and (200) to... Figure 3 (c) cannot be observed, but through crystal plane (100), it can be seen that the structural characteristic peaks of the metal loading exhibit a certain degree of shift. In summary, the support preparation method and catalyst synthesis strategy adopted in this invention do not damage the molecular sieve structure and can effectively and uniformly load the transition metal oxide components onto the catalyst surface. Detailed Implementation

[0041] To make the contents of this invention easier to understand, the invention will be described in detail below with reference to the accompanying drawings and specific examples.

[0042] Metal oxide@HZSM-5 and SBA-15 molecular sieve composites are synthesized using a mechanical synthesis strategy to combine two molecular sieves with different pore sizes into a composite micro-mesoporous molecular sieve support, and load non-precious metal components, thereby reducing the cost of the system and improving the efficiency of the reaction.

[0043] To achieve the above objectives, the present invention provides the following solution, with the following steps:

[0044] Step (1):

[0045] Two molecular sieves, HZSM-5 and SBA-15, were mechanically synthesized to obtain a composite catalyst support. The support, metal source, and deionized water were then mixed and impregnated to obtain a precursor. Subsequently, the precursor was calcined at 350–500 °C, and further at 400–450 °C, to obtain the composite supported catalyst. The metal source was one of iron, chromium, cobalt, or manganese, preferably at least one of the corresponding metal ions, such as nitrate, sulfate, organic acid salt, or chloride.

[0046] The composite supported catalyst is a metal@composite molecular sieve material, comprising two molecular sieves, HZSM-5 and SBA-15, and a multivalent metal oxide supported thereon.

[0047] Step (2):

[0048] HMF, alkali, and oxidant were catalytically oxidized and converted under the composite catalyst in step (1). The product was centrifuged at 8000-12000 rpm for 5-10 min, and the supernatant was taken for high performance liquid chromatography analysis of the contents of HMF and FDCA. The solid phase was washed with deionized water 3-5 times and then dried in an oven at 50-70℃ for 10-13 h for a cycle experiment.

[0049] The oxidant is one of oxygen, ozone, hydrogen peroxide, and peroxide.

[0050] The alkali is at least one of an alkali metal bicarbonate or ammonia water.

[0051] The yields of HMF and FDCA were determined by high performance liquid chromatography (HPLC).

[0052] Example 1:

[0053] (1) HZSM-5 (represented by the code Z) and SBA-15 (represented by the code S) were mechanically ground and mixed at a weight ratio of 2:1. Specifically, 1 / 4 of the total mass of 2g was taken at a ratio of 2:1 and ground for 5 minutes each time. After the fourth addition, the mixture was ground for 10 minutes, for a total of 25 minutes. This mixture was recorded as Z:S = 2:1 (mixture).

[0054] Weigh out Co(NO)₂·6H₂O and add it to 3 ml of water, stirring until the metal salt dissolves. Add 0.5 g of Z:S = 2:1 (controlling the weight ratio of Co to Z:S = 2:1 to 1:10, i.e., the loading of Co is 10%) and mix well. Let stand for 12 h. Then dry in an oven at 60 °C for 10 h, grind to obtain the precursor, and then calcine the precursor in a muffle furnace at 400 °C for 4 h to obtain a composite supported catalyst with an active component loading of 10%, denoted as Co-Z:S = 2:1.

[0055] (2) Take 0.02g of the above catalyst, 0.02g of HMF, 0.05g of NaHCO3 and 20ml of deionized water and add them to a stainless steel high-pressure reactor. Seal the container, purge the air into the reactor and then introduce oxygen. Set the temperature to 140℃, the O2 pressure to 1.0Mpa, and the stirring speed to 200rpm. After the hydrothermal catalytic oxidation reaction is carried out for 10 hours, the reactor is placed in water and rapidly cooled to room temperature. Then, the product is centrifuged at 10000rpm and the liquid phase is taken for high performance liquid chromatography analysis to detect the contents of HMF and FDCA. The corresponding conversion rate and yield are calculated to be 94.93% and 35.03%, respectively. The solid phase is washed 5 times with deionized water, dried in an oven at 70℃ for 12h and then subjected to a cycle experiment.

[0056] Example 2:

[0057] Compared to Example 1, the only difference is that the total amount of HZSM-5 and SBA-15 remains the same, but the ratio of the two is changed. The experimental groups are as follows:

[0058] Group A: The ratio of Z / S is 1:2;

[0059] Group B: The ratio of Z / S is 1:1;

[0060] Group C: The ratio of Z to S is 3:1.

[0061] All other operations and parameters are the same as in Example 1, and the results are as follows:

[0062] Group A: HMF conversion rate was 92.84%, and FDCA yield was 29.87%;

[0063] Group B: HMF conversion rate was 94.05%, and FDCA yield was 32.18%;

[0064] Group C: HMF conversion rate was 93.54%, and FDCA yield was 30.64%.

[0065] Example 3:

[0066] Compared with Example 1, the difference between groups A, B, and C is that the transition metal composition was changed, while the total metal loading and other operating conditions remained the same as in Example 1. The experimental groups are as follows:

[0067] Group A: Metal M is Fe;

[0068] Group B: Metal M is Cr;

[0069] Group C: Metal M is Mn;

[0070] Group D: Combination metals Co and Mn (Co / Mn elemental weight ratio is 1:1).

[0071] The results are as follows:

[0072] Group A: HMF conversion rate was 88.04%, and FDCA yield was 25.48%;

[0073] Group B: HMF conversion rate was 89.15%, and FDCA yield was 26.52%;

[0074] Group C: HMF conversion rate was 86.16%, and FDCA yield was 28.76%;

[0075] Group D: HMF conversion rate was 91.82%, and FDCA yield was 70.33%.

[0076] As can be seen from Examples 1 and 3, the preferred Co / Mn combination can unexpectedly achieve synergy, which can further improve the yield of FDCA.

[0077] Example 4:

[0078] Compared with Example 1, the difference lies in changing the amount of transition metal source used, thereby improving its loading. All other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0079] Group A: Co loading is 5%;

[0080] Group B: Co loading is 15%;

[0081] The results are as follows:

[0082] Group A: HMF conversion rate was 93.61%, and FDCA yield was 31.56%;

[0083] Group B: HMF conversion rate was 92.84%, and FDCA yield was 30.77%.

[0084] Example 5

[0085] Compared with Example 1, the only difference is that the oxidation time in step 2 is changed; all other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0086] Group A: Reaction time is 12 hours;

[0087] Group B: Reaction time is 24 hours;

[0088] The results are as follows:

[0089] Group A: HMF conversion rate was 95.34%, and FDCA yield was 42.68%;

[0090] Group B: HMF conversion rate was 96.6%, and FDCA yield was 55.06%.

[0091] Example 6

[0092] Compared to Example 1, the only difference is that several parameters have been changed. The key difference is:

[0093] In step 1, the calcination temperature was 450℃ and the time was 3 hours. In step 2, the weight ratio of HMF, catalyst, and sodium bicarbonate was 1:1.2:1.2.5; the reaction temperature was 130℃ and the oxygen pressure was 1.2 MPa. Other operations and parameters were the same as in Example 1. The results showed that the conversion rate of HMF was 95.01% and the yield of FDCA was 36.32%.

[0094] Comparative Example 1

[0095] Compared with Example 1, the only difference is that SBA-15 is missing, and the missing amount is made up by HZSM-5 in equal amounts. Other operations and parameters are the same as in Example 1.

[0096] The HMF conversion rate was 90.80%, and the FDCA yield was 19.76%.

[0097] Comparative Example 2

[0098] Compared with Example 1, the only difference is that HZSM-5 is missing, and the missing amount is made up by an equal amount of SBA-15.

[0099] Other operations and parameters are the same as in Example 1.

[0100] The HMF conversion rate was 89.91%, and the FDCA yield was 19.13%.

[0101] Comparative Example 3

[0102] Compared with Example 1, the only difference is that the HZSM-5 and SBA-15 in the specified proportions are sintered and then physically mixed with cobalt oxide (the amount of cobalt is the same as in Example 1).

[0103] The HMF conversion rate was 87.23%, and the FDCA yield was 13.72%.

[0104] Comparative Example 4

[0105] Compared with Example 1, the only difference is that HZSM-5 and 50% of cobalt are subjected to the calcination treatment described above, and SBA-15 and the remaining 50% of cobalt are subjected to the calcination treatment described above. The calcined products are then physically mixed, wherein the ratio of HZSM-5 and SBA-15 is the same as in Example 1.

[0106] The HMF conversion rate was 89.12%, and the FDCA yield was 17.21%.

[0107] The above description of the experimental examples is intended to enable those skilled in the art to understand and use the invention. The invention is not limited to the above experimental examples. All improvements and modifications made in accordance with the claims of this invention are within the scope of this invention.

Claims

1. A method for synthesizing FDCA, characterized in that, FDCA is prepared by catalytic oxidation of HMF, alkali, oxidant and catalyst; The alkali is at least one of an alkali metal bicarbonate and ammonia water; The weight ratio of HMF, base, and catalyst is 1:1.25~3:0.5~1.5; The oxidant is a gaseous oxidant; the oxygen partial pressure during the catalytic oxidation stage is controlled at 0.6~1.8 MPa; The temperature for the catalytic oxidation reaction is 100~160℃; the reaction time is more than 8 hours. The catalyst is a transition metal oxide@HZSM-5 / SBA-15 composite catalyst, which is prepared by calcining HZSM-5, SBA-15 and transition metal source at a temperature of ≥350℃ in an oxygen-containing atmosphere. The transition metal element in the transition metal source includes at least one of iron, chromium, cobalt, and manganese; The weight ratio of HZSM-5 to SBA-15 is 1~3:1~2; The loading of transition metal elements in the transition metal source in the transition metal oxide@HZSM-5 / SBA-15 composite catalyst is 5~15 wt.

2. The method for synthesizing FDCA as described in claim 1, characterized in that, The transition metal elements in the transition metal source include two or more of iron, chromium, cobalt, and manganese.

3. The method for synthesizing FDCA as described in claim 1, characterized in that, The transition metal elements in the transition metal source include cobalt and manganese; wherein the elemental weight ratio of cobalt and manganese is 1~2:1~2.

4. The method for synthesizing FDCA as described in claim 1, characterized in that, The transition metal source is at least one of the following: nitrate, sulfate, organic acid salt, and chloride salt of a transition metal element; The composite method is either solid-phase composite or wet impregnation.

5. The method for synthesizing FDCA as described in claim 1, characterized in that, The roasting atmosphere is an air atmosphere.

6. The method for synthesizing FDCA as described in claim 5, characterized in that, The roasting temperature is 350~500℃.

7. The method for synthesizing FDCA as described in claim 6, characterized in that, The roasting temperature is 400~450℃.

8. The method for synthesizing FDCA as described in claim 1, characterized in that, The roasting time is 2 to 5 hours.

9. The method for synthesizing FDCA as described in claim 1, characterized in that, The temperature for the catalytic oxidation reaction is 130~150℃.

10. The method for synthesizing FDCA as described in claim 1, characterized in that, The catalytic oxidation reaction takes 10-24 hours.

Citation Information

Patent Citations

  • Method for preparing 2,5-furandicarboxylic acid by supported bifunctional catalyst by catalyzing fructose

    CN105418561A

  • Monatomic palladium catalyst as well as preparation method thereof and method for preparing 2,5-FDCA by catalyzing oxidation of 5-HMF

    CN109046349A

  • Preparation method of 2,5-furandicarboxylic acid under mild condition

    CN112830916A

  • Green synthesis method for preparing 2, 5-furandicarboxylic acid by catalyzing series oxidation of 5-hydroxymethylfurfural

    CN115785037A